Pentingnya Perencanaan Keuangan bagi Pelaku Usaha Mikro Kecil dan Menengah di Desa Tiwulandu, Brebes - Slamet Bambang Riono Slamet; Dumadi; Anisa Sains Kharisma (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Financial management ability in terms of financial planning is one of the abilities that must be possessed by Micro, Small and Medium Enterprises (MSMEs) by increasing their financial planning knowledge. The existence of good financial management capabilities can carry out effective, efficient, and useful financial planning, so that business actors are expected to increase the level of welfare in running their business. This community service activity is carried out with the aim that MSME actors have good financial planning knowledge. This community service activity uses the method of material presentation, discussion and question and answer. The result of this activity is that business actors can carry out financial planning on their business activities. By having good financial planning knowledge, business actors in Tiwulandu Village, Brebes are expected to be more advanced, smooth, and prosperous in running their businesses.